Clough, Emerson, and knowingness - McGhee, F (Oxford University Press, 2020)
The poetry of Arthur Hugh Clough has tended to be read in dialogue with the writings of his friend and critic, Matthew Arnold. This essay explores how bringing Clough’s work into conversation with that of a very different friend, Ralph Waldo Emerson, offers to cast his intellectual affinities and poetic technique in a new light. Interweaving close readings of Clough’s verse with detailed attention to the essays he is known to have read and admired, I trace how Clough adapts and revises Emerson’s critique of ‘knowingness’. Beginning by tracing the history of this term in nineteenth-century literature and culture, I argue that Clough’s Dipsychus shapes an Emersonian ethic and aesthetic of encounter as an alternative to complacent and proprietorial forms of knowing. Turning to the rest of Clough’s oeuvre, especially Amours de Voyage, I then consider how fantasies of the future are central to what it means to be knowing about oneself, and examine how Clough applies poetic pressure to Emerson’s conviction that ‘A man … never rises so high as when he knows not whither he is going’.